Acute mesenteric ischaemia due to superior mesenteric vein (SMV) thrombosis. Issue 4 (1st April 2021) - Ahmad, Muhammad Salah Muhammad; Iqbal, Muhammad Rafaih; Refson, Jonathan Simon
Abstract : A 77-year-old male patient presented with a 5-day history of abdominal pain, coffee ground vomiting and blood-stained diarrhoea. CT scan of the abdomen and pelvis demonstrated a long segment thrombotic occlusion of the superior mesenteric vein (SMV) extending up to the proximal portion of the portal vein causing significant acute small bowel ischaemia. Patient's deteriorating clinical condition warranted surgical management. Successful surgical management required multidisciplinary teamwork between emergency, vascular surgeons, anaesthetists and intensivists. Emergency laparotomy revealed gangrene of an estimated 120 cm of small bowel segment starting from duodenojejunal junction and a long segment thrombotic occlusion of the SMV extending up to the portal confluence. Resection of gangrenous small bowel without anastomosis and thrombo-embolectomy of SMV along with laparostomy was done at the initial operation. Patient was admitted in the intensive care unit on systemic heparinisation through intravenous administration of unfractionated heparin. Second relook exploration was done after 48 hours followed by anastomosis of the small bowel and closure of the abdomen. Patient made a good recovery following anticoagulation therapy and was discharged on postoperative day 10.